Features of aflibercept plus hyperbaric oxygen therapy for diabetic macular edema - V. O. Drozdov; V. M. Sakovych (Ukrainian Society of Ophthalmologists, 2022)
Background: Diabetes mellitus (DM) is a disease characterized by chronic hyperglycemia and a cascade of pathological vascular alterations leading to diabetic retinopathy (DR) and diabetic macular edema (DME). Purpose: To compare clinical characteristics in patients treated with aflibercept only and in those treated with aflibercept plus hyperbaric oxygen (HBO) therapy for DME. Material and Methods: This open-label case-control study involved 91 type 2 diabetic (DM2) patients with non-proliferative DR and DME. Patients of the aflibercept-only group received a monthly intravitreous aflibercept at a dose of 2 mg for 5 months. Patients of the aflibercept-plus-HBO group received a monthly intravitreous aflibercept at a dose of 2 mg for 3 months. In addition, the latter patients received ten HBO sessions in the period between the first and the third injections. All patients underwent a routine general clinical and eye examination. Results: At 3 months and 6 months, patients in the aflibercept-plus-HBO group showed improvements in visual acuity by 28.81% and 7.14%, respectively (р < 0.05), and retinal sensitivity to light by 24.44% and 19.5%, respectively (р < 0.05), with a reduction in the number of patients with DME by 84.56% and 51.13%, respectively (p < 0.05). Conclusion: Intravitreal aflibercept with adjunctive HBO provides improved efficacy of treatment for DME in patients with DM2, with reductions in (a) the number and risk of intravitreal injections, (b) drug load on the patient, and (c) treatment duration.